2015
DOI: 10.1016/j.bbr.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to HIV-1 Tat in brain impairs sensorimotor gating and activates microglia in limbic and extralimbic brain regions of male mice

Abstract: Human immunodeficiency virus (HIV) infection is associated with mood disorders and behavioral disinhibition. Impairments in sensorimotor gating and associated neurocognitive disorders are reported, but the HIV-proteins and mechanisms involved are not known. The regulatory HIV-1 protein, Tat, is neurotoxic and its expression in animal models increases anxiety-like behavior concurrent with neuroinflammation and structural changes in limbic and extra-limbic brain regions. We hypothesized that conditional expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 53 publications
3
41
1
2
Order By: Relevance
“…This notion is in consistence with previous studies that virus, Tat and gp120 may directly contribute to HAND (Paris et al 2015;Podhaizer et al 2012;Zou et al 2007). Because gp120 glycoproteins can be taken up by brain microvessels and transported across the BBB (Banks et al 2005), it is possible that higher brain P24 antgenemia in HIV-1 JR-FL -infected mice contribute to severer neuron damages as compared with HIV-1 BJZS7 -infected animals.…”
Section: Discussionsupporting
confidence: 53%
“…This notion is in consistence with previous studies that virus, Tat and gp120 may directly contribute to HAND (Paris et al 2015;Podhaizer et al 2012;Zou et al 2007). Because gp120 glycoproteins can be taken up by brain microvessels and transported across the BBB (Banks et al 2005), it is possible that higher brain P24 antgenemia in HIV-1 JR-FL -infected mice contribute to severer neuron damages as compared with HIV-1 BJZS7 -infected animals.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally microglial cell induction of inflammosomes (innate immune response protein complexes that respond to pathogen associated molecular patterns) is precipitated during acute lentiviral infection, and inflammosome activation associates with brain pathology in a feline immunodeficiency model of HIV encephalitis [52]. Finally, HIV-Tat protein may be a direct trigger or in a pathway associated with processes leading to microglial activation, though the extent to which this is an important cause of ongoing activation in latent cART treated infection is unclear [53, 54]. Overall, this new understanding of the homeostasis and behavior of microglia supports their major role in contributing to the problem of persistent CNS immune activation in HIV: microglia respond to acute HIV in an immediate and dynamic fashion, and once perturbed they are resident cells of the CNS that may harbor integrated HIV long-term, associated with constant cellular immune activation.…”
Section: Immune Cells and Tissues Involved In Pathogenesismentioning
confidence: 99%
“…URB602, JZL184, AM5206) produce neuroprotective effects both in vitro (Chen et al, 2011; Naidoo et al, 2011) and in vivo (Lara-Celador et al, 2012; Naidoo et al, 2011), but their effects in models of neuro-acquired immune deficiency syndrome (neuroAIDS) are little explored. The HIV-1 protein transactivator of transcription (Tat) likely contributes to synaptodendritic injury observed in brains of HIV-1 infected individuals (Jones et al, 2000; Valle et al, 2000) and has been shown to cause dendritic structural and functional defects in vitro (Bertrand et al, 2013; Bertrand et al, 2014; Fitting et al, 2014; Haughey et al, 1999; Haughey et al, 2001; Kruman et al, 1998) and in vivo (Carey et al, 2012; Fitting et al, 2013; Fitting et al, 2010; Hahn et al, 2013; Paris et al, 2015). Tat activates both glutamatergic NMDA receptors (GluNs) (Aksenov et al, 2012; Fitting et al, 2014; Haughey et al, 2001; Li et al, 2008; Magnuson et al, 1995; Perez et al, 2001) and AMPA receptors (GluRs) (Longordo et al, 2006), leading to increased excitability (Brailoiu et al, 2008; Fitting et al, 2015; Ngwainmbi et al, 2014) as well as increases in [Na + ] i , mitochondrial instability, and excessive Ca 2+ influx (Fitting et al, 2014; Yu and Salter, 1998), all of which eventually cause dendritic swellings (Bertrand et al, 2014; Fitting et al, 2014).…”
Section: Introductionmentioning
confidence: 99%